Experimental Uveitis in Dogs : Comparison of Topical Ketorolac Tromethamine Versus Flurbiprofen - Faierstein Teixeira, Cristiane; do Rocio Binder do Prado, Antonia Maria; Rossetto, Victor José Vieira; Pinheiro Ferreira, João Carlos; Fernando Moreto,; Teixeira Neto, Francisco José; Zanuzzo, Felipe Sabbadin; Seullner Brandão, Claúdia Valéria; Gomes Quitzan, Juliany (Acta Scientiae Veterinariae, 2026)
Background: Topical anti-inflammatory medication is the 1st choice to treat anterior uveitis, considered one of the most common eye disease in dogs. The inflammatory process must be controlled because when exacerbated it may cause pain, glaucoma, retinal degeneration and blindness. Among the topical non-steroidal anti-inflammatory drugs used in veterinary medicine, flurbiprofen and ketorolac tromethamine are highlighted. Flurbiprofen and ketorolac are important to treat uveitis, but ketorolac has not been widely studied in dogs. The aim of this study was to evaluate the effect of 0.5% ketorolac tromethamine versus 0.03% flurbiprofen in the dog’s eye submitted to experimental uveitis. Materials, Methods and Results: The study was a crossover, descriptive and randomized clinical trial. Ten healthy adult (4 ± 3 years old) mongrel dogs (4 neutered male and 6 spayed female) were used and each dog received a double procedure (on the right and left eyes), using 2 different treatments, performed in a blind fashion. It was administrated 0.5% ketorolac tromethamine and 0.03% flurbiprofen, respectively, on the right and left eyes. Paracentesis of the anterior chamber was performed to induce uveitis on the right eye. An aliquot of 0.2 mL of the AH was collected at M0 and after 30 min (M1). At this time, one ketorolac drop was instilled, and another aliquot of 0.3 mL of the AH was collected 30 min later (M2). Five days later (washout), the same procedure was carried out on the left eye, followed by treatment with flurbiprofen. Aqueous humor samples were collected to measure the PGE2 concentration by competitive enzyme immunoassay, and to quantify ketorolac or flurbiprofen by High-performance liquid chromatography (HPLC) method. Ophthalmic examination and Intraocular Pressure (IOP) measurement using Goldmann tonometer were performed 12, 24, 36, 48 and 60 h after M2. All animals were treated with ketorolac and flurbiprofen eye drops (right and left eye respectively), 4 times daily up to 60 h. IOP was not significantly different from the baseline values. Mean levels of PGE2 decreased in both treated eyes without significant difference. HPLC showed that the concentration of flurbiprofen and ketorolac were also not significantly different. Discussion: It is believed that IOP measurements of both treated eyes were not different from the basal values because the measurement was performed 8 h after the last paracentesis, when the treatments had already started. The time elapsed associated with the anti-inflammatory effect of both eye drops, therefore, may have been sufficient to restore the pressure after paracentesis and rupture of the blood-aqueous barrier. PGE2 level in the AH has been used to evaluate the effectiveness of anterior uveitis treatments. PGE2 decreases in the present study confirm that flurbiprofen and ketorolac were effective to control the inflammatory process induced by paracentesis. The anti-inflammatory effect of ketorolac tromethamine was probably attributed to satisfactory penetration in the anterior chamber. The results indicated that 0.5% ketorolac tromethamine had penetration and detectable concentrations in AH of dogs. Topically applied 0.5% ketorolac tromethamine was as effective as flurbiprofen to control ocular inflammation. Further studies are needed to consolidate the information on the pharmacokinetics and pharmacodynamics of this drug in dogs. Keywords: topical anti-inflammatory drug, Blood-aqueous barrier, Aqueous humor, eye.